2007
DOI: 10.1360/jos182153
|View full text |Cite
|
Sign up to set email alerts
|

A Method of Time Constraint Workflow Model Analysis and Verification

Abstract: In order to describe the temporal aspect of workflow model and verify the temporal consistency, a method based on temporal logic and model checking for modeling and verifying time constraint workflows is presented. By this method, the first order logic is used to model workflow including its basic temporal information, temporal logic is used to model the time constraints, and model checking is used to analyze and verify the temporal consistency. The method can be used to verify any time constraints that can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…13 C MAS NMR spectroscopy reveals the formation of a phenol-carbonate complex (d ¼ 162.00 ppm) upon exposure to CO 2 , which is in accordance with literature results for the monomolecular system. 12 The obtained spectrum also indicates that gaseous or physically coordinated CO 2 , which has a chemical shi at d ¼ 124.88 ppm, 32 is practically absent from the polyelectrolyte sample. An additional shi at d ¼ 158.28 ppm is ascribed to tetraalkylphosphonium bicarbonate formation in the presence of residual moisture (Fig.…”
Section: Substances [P 66614 ][2a] [P 66614 ][2b] and [P 66614 ]mentioning
confidence: 69%
See 2 more Smart Citations
“…13 C MAS NMR spectroscopy reveals the formation of a phenol-carbonate complex (d ¼ 162.00 ppm) upon exposure to CO 2 , which is in accordance with literature results for the monomolecular system. 12 The obtained spectrum also indicates that gaseous or physically coordinated CO 2 , which has a chemical shi at d ¼ 124.88 ppm, 32 is practically absent from the polyelectrolyte sample. An additional shi at d ¼ 158.28 ppm is ascribed to tetraalkylphosphonium bicarbonate formation in the presence of residual moisture (Fig.…”
Section: Substances [P 66614 ][2a] [P 66614 ][2b] and [P 66614 ]mentioning
confidence: 69%
“…The Dai group recently reported that CO 2 capacity of phenolic ILs can be tuned by substitution of electron-donating or -withdrawing groups at the phenyl ring, thereby controlling the Lewis-acidity of the phenolate moiety. 12 In an effort to further enhance CO 2 solubility, the concept was applied to the polymeric system. Surprisingly, the presence of electron-donating methoxy groups at the phenyl ring had an adverse effect on CO 2…”
Section: Phenol Modicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, CO 2 absorption into, and release from these IL could be repeatedly cycled 25 times with high absorption capacity. [8][9][10][11][12] Nonetheless, these functionalized ILs were not easy to synthesize and purify.…”
Section: Ionic Liquids -Impact On Old and New Energy Technologiesmentioning
confidence: 99%
“…18 It was shown that this salt-bridge formation can be avoided by developing aprotic heterocyclic anions (AHA) which lack the necessary proton to form salt bridges as reported by Wang. 11,19,20 These AHA ILs may then be used to efficiently and reversibly capture CO 2 in equimolar stoichiometry without the increase in viscosity. 21,22 The new ILs can be prepared from simple azoles and can be tuned for stability, CO 2 absorption enthalpy, and CO 2 capacity based on the choice of the azole.…”
Section: Introductionmentioning
confidence: 99%